Physical literacy in school aged children: a preliminary analysis relating health factors - Mayordomo-Pinilla, Noelia; Sánchez-Miguel, Pedro Antonio; Galán-Arroyo, Carmen; Castillo-Paredes, Antonio; Rojo-Ramos, Jorge (Frontiers in Public Health, 2025)
IntroductionAdolescents with high physical literacy (PL) have better health including cardiovascular fitness and reduced obesity. Improving these skills can lead to a healthier adulthood and reduce the risk of developing chronic diseases. However, physical activity (PA) levels are alarmingly low and PL has been proposed as a tool to improve them. This study aimed to investigate PL in school students [aged between 8 and 18 years (M = 13.08)] in southwestern Spain, explore sex differences and school location, and explore the correlations among PL, age, and Body Mass Index (BMI).MethodsThe Mann-Whitney U test was applied to determine the differences in the PPLI-Q according to sex and school location variables and the Bonferroni correction. Spearman's Rho was also applied to determine the correlations between PL and BMI and age, determining the effect size using Hedge's g for sex and high school location. Results: The results showed significant differences in sex and high school location in favor of boys (M = 4.12, SD = 0.56) and rural settings (M = 4.11, SD = 0.52). The correlation between BMI and PL was significant, with an inverse and medium effect (BMI, ρ = −0.102, p = 0.006*).DiscussionThese results suggest that females have a lower PL perception, and its correlation with BMI underscores the importance of intervention in improving their health. It is also important to intervene in the same way in older students and those with a higher BMI to improve their PL and increase their PA practices to establish healthier habits.